Calculated brightness temperatures of solar structures compared with ALMA and Metsähovi measurements - Matković, Filip; Brajša, Roman; Kuhar, Matej; Benz, Arnold O.; Ludwig, Hans-Günter; Selhorst, Caius L.; Skokić, Ivica; Sudar, Davor; Hanslmeier, Arnold (Astronomische Nachrichten, 2024)
The Atacama Large Millimeter/submillimeter Array (ALMA) allows for solar observations in the wavelength range of 0.3-10 mm, giving us a new view of the chromosphere. The measured brightness temperature at various frequencies can be fitted with theoretical models of density and temperature versus height. We use the available ALMA and Metsähovi measurements of selected solar structures (quiet sun (QS), active regions (AR) devoid of sunspots, and coronal holes (CH)). The measured QS brightness temperature in the ALMA wavelength range agrees well with the predictions of the semiempirical Avrett-Tian-Landi-Curdt-Wülser (ATLCW) model, better than previous models such as the Avrett-Loeser (AL) or Fontenla-Avrett-Loeser model (FAL). We scaled the ATLCW model in density and temperature to fit the observations of the other structures. For ARs, the fitted models require 9%-13% higher electron densities and 9%-10% higher electron temperatures, consistent with expectations. The CH fitted models require electron densities 2%-40% lower than the QS level, while the predicted electron temperatures, although somewhat lower, do not deviate significantly from the QS model. Despite the limitations of the one-dimensional ATLCW model, we confirm that this model and its appropriate adaptations are sufficient for describing the basic physical properties of the solar structures.
Zuerst veröffentlicht: 28. Februar 2024
Gesehen am 31.07.2024